Problems of Health Protection of Students with Health Limitations in Educational Institutions of the Russian Federation - Svetlana B. Lazurenko; Tatiana A. Solovyova; Rimma N. Terletskaya; Svetlana R. Konova (National Research Mordova State University, 2021)
Introduction. The current legal framework for the education of children with health limitations was created after the conceptual provisions and international acts to ensure equal children's opportunities and access to free educational services without any type of discrimination. Regulatory documents contain the general rules for organization of educational activities and medical support in an educational institution, without specific recommendations for health strengthening and preservation of children with health limitations, taking into account the nature and severity of the disorder, as well as the combination thereof, which is a separate urgent state problem. This study was initiated to analyze the current situation with health protection of special needs children in educational institutions. The detection of organizational difficulties and legal restraints will allow to determine the remedial measures and prepare the proposals for the improvement of the educational system. Materials and Methods. The content analysis of the applicable regulatory legal documents of the Ministry of Health, the Ministry of Education and Science of the Russian Federation between 2012-2020 revealed urgent problems pertinent to the enforcement of legislative initiatives in the field of education and health protection of students with health limitations in various educational environments. Results. The study confirmed the hypothesis of the variability of the current organizational problems regarding health strengthening and preservation of students in an educational organization, including the weak legal and regulatory framework. The health-preserving environment of an educational organization is proved to have a combination of factors: availability of special educational and technical equipment to meet special educational needs of students, taking into account the severity of the physical dysfunction; the compliance of the tightness of timetable, number of lessons and the educational load with children's health state and individual psychological capabilities; availability of separate rest and restoration rooms; availability of up-to-date rehabilitation equipment for health strengthening of children with health limitations in the educational institution's environment; staffing with teachers and medical specialists who are aware of modern technologies of handling children with health limitations. Discussion and Conclusion. The study results can be facilitative of the development of the system of monitoring during the organization of the educational process and the variability of health protection conditions for students with health limitations in an educational organization as the method of prompt detection and elimination of adverse factors and, hence, mitigation of social risks and solving of one of the priority state tasks.